Enhancement of Regeneration Efficiency through Callus Induction Media Using 2,4-Dicholorophenoxyacetic acid in Indica Rice (Oryza sativa L. var. Ciherang) - Azizah, Kunti Anis; Restanto, Didik Pudji; Sugiharto, Bambang (Jurnal ILMU DASAR, 2017)
Indica rice variety Ciherang is the most planted variety in Indonesia, but the micropropagation technique is restricted because it is known has low regeneration frequency and included as recalcitrant cultivar for tissue culture and tranformation activities. One of solution to resolve that problem is developing a technique of somatic embryogenesis in callus of ciherang rice cultivar. The aims of study were to determine medium composition for inducting embryogenic callus in Ciherang rice and to know the effectivity of rice regeneration using callus as explant. The methods were included induction of embryogenic callus in callus induction media (CIM) containing MS basal, Proline 600 mg/l, Casein Hidrolisat 300 mg/l, phytagel 2,5 g/l, BAP 0.25 mg/l, sukrosa 30 %, and 2,4-D in different concentration, from 2,4-D 0 mg/l as control (CIM 1), 2,4-D 2 mg/l (CIM 2), 2,4-D 3 mg/l (CIM 3), and 2,4-D 4 mg/l (CIM 4). It then be continued to regenerate the calli in RM 1 medium containing MS basal, NAA 0,2 mg/l, Kinetin 2 mg/l, Agarose 10 g/l, and sukrosa 30 %, pH 5,8 for six days in dark and RM2 medium containing MS basal , NAA 0,2 mg/l, Kinetin 2 mg/l, Agarose 8 g/l, sukrosa 30 %, pH 5,8 in light room. Results showed CIM 4 medium using 2,4-D 4 mg/l gave optimum result in calli induction with procentage 57,63% and CIM 3 using 2,4-D 3 mg/l gave optimum result in embryonic calli induction with procentage 53,63%. Result of embryonic calli gave regeneration frequency procentage is 9,6%. The total planlet obtained after five weeks old in regeneration medum were 11 planlets ready for aclimatization. Keywords: Somatic embryo, Indica rice (Oryza sativa L. var. Ciherang), Callus